Emerging EdTech media impact: Enhancing science learning engagement in junior high school - Dessy Setyowati; Muhammad Aqmal Nurcahyo; Novaria Nusantara; Arie Susanty; Hendra Wijaya (Jurnal Pendidikan Informatika dan Sains, 2026)
This study aims to analyze the impact of Emerging Educational Technology (Emerging EdTech) media on student engagement in science learning at junior secondary schools located in the rural–urban transitional area of Kubu Raya Regency. The study employed a quantitative approach using a quasi-experimental design with a nonequivalent control group design. The sample consisted of 205 seventh-grade students divided into an experimental group (utilizing Emerging EdTech media) and a control group (utilizing H5P interactive video). Student engagement data were collected through a questionnaire based on Keller’s ARCS motivational model and behavioral observation sheets. The results indicated that the mean engagement score of students in the experimental group reached 3.26, which was higher than that of the control group at 2.98. The Independent Samples T-Test yielded a significance value of 0.000 (ρ < 0.05), indicating a statistically significant difference between the two groups. These findings suggest that the integration of Emerging EdTech media can influence student engagement in science learning. The study recommends the provision of immersive technology-based digital hands-on experiences as a strategic approach to transforming science education in secondary schools.